Guinea : Technical Assistance Report-External Sector Statistics. (IMF Staff Country Reports; Country Report ;, 2020)
The fourth and last technical assistance (TA) mission for the benefit of Guinea, under the project on improving external sector statistics (ESS) in 17 Francophone countries of West and Central Africa, funded by the Japanese government and administered by the IMF, took place in Conakry during August 26-30, 2019. The mission was hosted by the Central Bank of the Republic of Guinea (BCRG), which is the institution responsible for compiling the ESS. The main points addressed by the mission were to support (i) the process of participating in the coordinated direct investment survey (CDIS), (ii) the detailed technical work for improving the current and financial accounts, and (iii) the implementation of recommendations from previous missions.